2020
DOI: 10.18632/aging.102681
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquinol-10 delays postovulatory oocyte aging by improving mitochondrial renewal in pigs

Abstract: Ubiquinol-10, the reduced form of coenzyme Q10, protects mammalian cells from oxidative damage and enhances mitochondrial activity. However, the protective effect of ubiquinol-10 on mammalian oocytes is not well understood. In this study, we investigated the effect of ubiquinol-10 on porcine oocytes during postovulatory aging. Metaphase II oocytes were selected as fresh oocytes and further cultured for 48 h with different concentrations of ubiquinol-10 (0-400 μM) in vitro as a postovulatory aging model. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 54 publications
1
34
0
1
Order By: Relevance
“…The spindle as an important structure for accurate chromosomal distribution, is correlated with coordination interaction between the actin and microtubule cytoskeleton. The aged oocytes often present with spindle disruption and actin reduction 55 . In the present study, Ax treatment attenuated the spindle abnormality and restored the actin expression for aged oocytes, indicating its protection on cytoskeletal stability.…”
Section: Discussionmentioning
confidence: 99%
“…The spindle as an important structure for accurate chromosomal distribution, is correlated with coordination interaction between the actin and microtubule cytoskeleton. The aged oocytes often present with spindle disruption and actin reduction 55 . In the present study, Ax treatment attenuated the spindle abnormality and restored the actin expression for aged oocytes, indicating its protection on cytoskeletal stability.…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulated mRNA expression of GDF9, BMP15, MOS, and CCNB1 suggested that IMP might be involved in regulating oocyte cytoplasmic maturation ( Su et al, 2004 ; De Castro et al, 2016 ; Liu et al, 2018 ), as well as promoting MPF activity ( Peter et al, 2002 ; Madgwick and Jones, 2007 ; Yang et al, 2017 ). Moreover, stable MOS and CCNB1 levels are essential for meiosis mediated by MAD1, MPS1, and APC/C Cdc 20 ( Alfonso-Pérez et al, 2019 ), as well as balancing the MAPK, NF-κB signal which affects the ROS and mitochondrial dysfunction-mediated oocyte aging ( Achache et al, 2020 ; Niu et al, 2020 ; Zhu et al, 2020 ). In addition, relatively high levels of GDF9 and BMP15 also help slow down the aging and reduce the apoptosis of oocytes by luteinizing hormone receptor, BCL2/BAX, connexin43-mediated regulating the steroidogenic acute regulatory protein expression, plasminogen activator, gap junctions ( Hussein et al, 2005 ; Chang et al, 2014 ; De Castro et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spindles and actin filaments of oocyte are sensitive to chemicals and aging ( Sun and Kim, 2012 ; Liang et al, 2018 ; Niu et al, 2020 ). Our results showed that the rate of abnormal spindle morphology in aged oocytes exposed to 40 μM IMP is markedly lower than that in control oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Spindles and actin filaments of oocyte are sensitive to chemicals and aging (Sun and Kim, 2012;Liang et al, 2018;Niu et al, 2020). Our results showed that the rate of abnormal spindle morphology in aged oocytes exposed to 40 µM IMP is markedly lower than that in control oocytes.…”
Section: Discussionmentioning
confidence: 60%
“…affects the ROS and mitochondrial dysfunction-mediated oocyte aging (Achache et al, 2020;Niu et al, 2020;Zhu et al, 2020). In addition, relatively high levels of GDF9 and BMP15 also help slow down the aging and reduce the apoptosis of oocytes by luteinizing hormone receptor, BCL2/BAX, connexin43-mediated regulating the steroidogenic acute regulatory protein expression, plasminogen activator, gap junctions (Hussein et al, 2005;Chang et al, 2014;De Castro et al, 2016).…”
Section: Discussionmentioning
confidence: 99%